Analisis Pola Konsumsi Masyarakat Kota Jambi Pada Bulan Ramadhan Mengunakan Pendekatan Smart PLs 3.0 - Habriyanto Habriyanto; Muhammad Yasir Nasution; Muhammad Yusuf Harahap (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
This research aims to look at the influence of factors that affect the consumption patterns of the community of the city of Jambi. The approach was conducted using smart analysis pls 3.0 to see lines of influence between formative and reflective variable in variable form the outer model and variable inner model. In this study using the 140 respondents with the outcome variable of influence lines reflective of Psychology factor variable indicator of attitudes, knowledge, perception and motives of the latent variable influence on psychology. While the influence of the outer line model formative factors of religiosity which consists of an indicator variable is unity, cleanliness, simplicity, cleanliness and latent variables affect the mandate factor religiosity and indicator variables for Justice, halal and the principle of generosity, morality has no effect against the latent variable factors of religiosity. Outer formative personal factor model consisting of demographic and situational variables influence on personal factors while variable engagement has no effect. Social factors in the form of structure of outer formative model is an indicator variable reference group, social class and cultural influence on latent from. Latent varibel consumption patterns of the community in the form of outer formative model variable indicator of prices of goods, the level of opinion, tastes, and advertising the products variable latent influence on consumption patterns of society whereas the variable indicator number of families have no effect. In the form of lines of influence of latent variable model of inner factors of influence on latent religiosity variable factors psychology, personal, social and societal consumption patterns of the city of Jambi in Ramadaan. To track social factors against the influential community consumption patterns while the latent variable factors of psychology and latent variable has no effect on personal factors. Determination of the coefficient of variation of the latent variable factors of religiosity was able to explain to the latent variable factors psychology, personal factors, social factors and consumption patterns each of 43.2%, 31.7% and 42.7%. Determination of the coefficient of the latent variable social factors capable of explaining the variation of the latent variable consumption patterns of the community of the city of Jambi in Ramadaan amounting to 61%. Results perhitugan Q square of a variation in the meaning of diversity 0913 model in the study of 91.3% and 8.7% is explained by his side other models outside of this research.